Positive electrode lithium supplement agent and preparation method thereof, positive electrode plate and lithium ion battery

By forming a double coating layer of borate and spinel phase materials on the Li5FeO4 matrix of the positive electrode lithium replenishing agent, and using the O-B-O bond to capture oxygen and prevent oxygen diffusion, the battery performance problem caused by the release of oxygen from Li5FeO4 delithiation is solved. Significantly improve the high temperature performance and cycle performance of the battery.

CN119340395APending Publication Date: 2025-01-21GUANGZHOU GREATER BAY TECH CO LTD

Patent Information

Application Number
CN202411453358.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The oxygen released by Li5FeO4 deliquency in existing positive electrode lithium supplements leads to problems such as gas production and poor high-temperature performance of the battery, and the high residual alkali value affects the battery performance.

Method used

A double-layer coated cathode lithium replenishing agent is used. The matrix is ​​Li5FeO4, the first coating layer is borate, and the second coating layer is spinel phase material. It captures oxygen through the O-B-O bond to prevent oxygen diffusion and promote lithium ions. transmission.

Benefits of technology

Effectively captures the oxygen released by delithiation of Li5FeO4, improves the high-temperature performance and cycle performance of the battery, reduces the residual alkali value, and avoids side reactions between active oxygen and electrolyte.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119340395A_ABST
    Figure CN119340395A_ABST
Patent Text Reader

Abstract

The invention relates to a positive electrode lithium supplement agent and a preparation method thereof, a positive electrode plate and a lithium ion battery, and belongs to the technical field of battery materials, the positive electrode lithium supplement agent comprises a matrix and a coating layer coating the surface of the matrix; the coating layer comprises a first coating layer coated on the surface of the base body and a second coating layer coated on the surface of the first coating layer; the matrix is Li5FeO4, and the matrix is Li5FeO4; the first coating layer is borate, and the second coating layer is a spinel phase material; the boron element in the first coating layer accounts for 0.1-0.3% of the mass of the matrix, and the second coating layer accounts for 0.1-0.3% of the mass of the matrix. The positive electrode lithium supplement agent provided by the invention can capture oxygen released by lithium removal of Li5FeO4, effectively improves the problems of gas production, poor high-temperature performance and the like of a battery caused by oxygen release in the existing lithium supplement process of Li5FeO4, and improves the high-temperature performance and cycle performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery materials, and in particular to a positive electrode lithium supplement and a preparation method thereof, a positive electrode sheet and a lithium ion battery. Background Art

[0002] At present, the lithium replenishment methods in batteries can be mainly divided into positive electrode lithium replenishment and negative electrode lithium replenishment. Among them, positive electrode lithium replenishment is to add a positive electrode lithium replenisher to the positive electrode system of the battery. At present, the positive electrode lithium replenisher is mainly lithium-rich materials such as Li5FeO4 and LiNO2. The lithium replenishing material in the Chinese patent CN109546226A is Li5FeO4. Although it has improved the capacity of the battery cell to a certain extent, its residual alkali value is relatively high. The oxygen released during the lithium replenishment process will form active oxygen and react with the electrolyte. At the same time, it also causes the residue of non-lithium source components (impurities) in the lithium replenishing material, which damages the battery performance and causes serious self-discharge of the battery cell and decreased discharge capacity. In addition, when preparing the positive electrode sheet, the higher residual alkali will react with the positive electrode binder polyvinylidene fluoride (PVDF), and chemical gelation is prone to occur during the stirring process of the slurry, which increases the viscosity of the slurry and affects the processing of the electrode sheet. Summary of the invention

[0003] In view of one or more technical problems existing in the prior art, the present invention provides a positive electrode lithium replenisher and a preparation method thereof, a positive electrode plate and a lithium ion battery. The positive electrode lithium replenisher provided by the present invention can capture the oxygen released by the delithiation of Li5FeO4, effectively improving the problems of battery gas production and poor high temperature performance caused by the release of oxygen in the existing Li5FeO4 lithium replenishment process, thereby improving the high temperature performance and cycle performance of the battery.

[0004] The present invention provides a positive electrode lithium supplement, the positive electrode lithium supplement comprises a substrate and a coating layer coated on the surface of the substrate; the coating layer comprises a first coating layer coated on the surface of the substrate and a second coating layer coated on the surface of the first coating layer;

[0005] The substrate is Li5FeO4; the first coating layer is borate, and the second coating layer is spinel phase material; the boron element in the first coating layer accounts for 0.1-0.3% of the mass of the substrate, and the second coating layer accounts for 0.1-0.3% of the mass of the substrate.

[0006] Preferably, the borate is lithium borate; and / or

[0007] The spinel phase material is selected from at least one of lithium nickel manganese oxide and lithium manganese oxide.

[0008] In a second aspect, the present invention provides a method for preparing the positive electrode lithium supplement agent according to the first aspect, the preparation method comprising:

[0009] The substrate is mixed with boric acid, and subjected to a first solid phase sintering to form a first coating layer on the surface of the substrate to obtain a first modified substrate;

[0010] The first modified matrix and the spinel phase material are mixed evenly, and subjected to a second solid phase sintering to form a second coating layer on the surface of the first coating layer to obtain a positive electrode lithium supplement.

[0011] Preferably, the mass ratio of the matrix to boric acid is 100:0.5-1.8.

[0012] Preferably, the mass ratio of the first modified matrix to the spinel phase material is 100:0.1-0.3.

[0013] Preferably, the first solid-phase sintering and the second solid-phase sintering are performed under a protective atmosphere, and the temperature of the second solid-phase sintering is lower than the temperature of the first solid-phase sintering; preferably, the protective atmosphere is an inert gas atmosphere, preferably a nitrogen atmosphere.

[0014] Preferably, the temperature of the first solid phase sintering is 500-700° C., preferably 600-650° C., and the time of the first solid phase sintering is 10-30 hours, preferably 15-25 hours; and / or

[0015] The temperature of the second solid-phase sintering is 400-600° C., preferably 450-550° C., and the time of the second solid-phase sintering is 10-40 hours, preferably 20-25 hours.

[0016] The present invention provides a positive electrode plate in a third aspect, wherein the positive electrode plate comprises the positive electrode lithium supplement agent described in the first aspect.

[0017] Preferably, the positive electrode lithium supplement accounts for 1 to 4 wt % in the positive electrode plate.

[0018] The present invention provides a lithium-ion battery in a fourth aspect, comprising the positive electrode sheet described in the third aspect.

[0019] Compared with the prior art, the present invention has at least the following beneficial effects:

[0020] The positive electrode lithium supplement agent provided by the present invention is based on Li5FeO4, and a borate coating layer (first coating layer) is coated on the surface of the substrate. By coating the borate coating layer on the surface of the substrate, an OBO bond is introduced, and the electron-deficient property of B is utilized to form a coordination bond with oxygen, so as to capture the oxygen released by the delithiation of Li5FeO4 during the first charging process, improve the effect of the subsequent side reaction of active oxygen with the electrolyte on the performance of the battery, and at the same time, reduce the residual alkali on the surface of the lithium supplement agent. A spinel phase coating layer (second coating layer) is coated on the surface of the borate coating layer (first coating layer), which can further prevent oxygen from diffusing outward from the lithium supplement agent and directly contacting the electrolyte, avoiding the effect of the side reaction of active oxygen with the electrolyte on the performance of the battery, and also avoiding the corrosion of the electrolyte to the Li5FeO4 substrate and the first coating layer, thereby affecting the performance of the battery. On the other hand, the three-dimensional lithium ion transmission channel of the spinel phase coating layer can promote the rapid transmission of lithium ions and thus facilitate rapid lithium supplementation. The positive electrode lithium replenisher provided by the present invention can effectively capture the oxygen released by Li5FeO4 during lithium depletion, avoid the side reaction of active oxygen with the electrolyte, and effectively improve the problems of battery gas production and poor high-temperature performance caused by the release of oxygen during the existing Li5FeO4 lithium replenishment process, thereby improving the high-temperature performance and cycle performance of the battery.

[0021] The preparation method of the positive electrode lithium supplement provided by the present invention adopts secondary solid-phase sintering. Since the sintering temperature affects the coating stability of the coating layer and the unit cell size formed by the final growth of the lithium supplement, the solid-phase sintering can promote the OBO bond formed between the matrix and the coating layer of the lithium supplement to have a stronger binding force, and the OBO bond is more stable in the lithium supplement, which is conducive to the lithium supplement to capture oxygen.

[0022] The lithium-ion battery assembled from the positive electrode sheet containing the above-mentioned lithium supplement provided by the present invention has excellent high-temperature storage gas production performance, high-temperature storage capacity retention rate and high-temperature cycle capacity retention rate, thereby improving the comprehensive performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0024] Figure 1 It is a schematic structural diagram of the positive electrode lithium supplement provided by the present invention. DETAILED DESCRIPTION

[0025] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0026] The present invention provides a positive electrode lithium supplement, the positive electrode lithium supplement comprises a substrate and a coating layer coated on the surface of the substrate; the coating layer comprises a first coating layer coated on the surface of the substrate and a second coating layer coated on the surface of the first coating layer;

[0027] The substrate is Li5FeO4; the first coating layer is borate, and the second coating layer is spinel phase material; the boron element in the first coating layer accounts for 0.1-0.3% of the mass of the substrate, and the second coating layer accounts for 0.1-0.3% of the mass of the substrate.

[0028] The positive electrode lithium supplement provided by the present invention uses Li5FeO4 as a matrix, a borate coating layer (first coating layer) is coated on the surface of the matrix, and a spinel coating layer is coated on the surface of the borate coating layer (first coating layer). By coating the borate coating layer on the surface of the matrix, an OBO bond is introduced, and the electron-deficient property of B is utilized to form a coordination bond with oxygen, so as to achieve the capture of oxygen released by the delithiation of Li5FeO4 during the first charging process, improve the influence of the subsequent side reaction of active oxygen and electrolyte on the performance of the battery, and at the same time, reduce the residual alkali on the surface of the lithium supplement. The spinel coating layer (second coating layer) is coated on the surface of the borate coating layer (first coating layer), which can further prevent oxygen from diffusing out of the lithium supplement and directly contacting the electrolyte, avoiding the influence of the side reaction of active oxygen and electrolyte on the battery performance, and also avoiding the influence of the corrosion of the electrolyte on the performance of the battery to the Li5FeO4 matrix and the first coating layer. On the other hand, the three-dimensional lithium ion transmission channel of the spinel phase coating layer can promote the rapid transmission of lithium ions and thus facilitate rapid lithium replenishment. The positive electrode lithium replenisher provided by the present invention can effectively capture the oxygen released by Li5FeO4 delithiation, avoid the side reaction between active oxygen and electrolyte, and effectively improve the problems of battery gas production and poor high temperature performance caused by the release of oxygen during the existing Li5FeO4 lithium replenishment process, thereby improving the high temperature performance and cycle performance of the battery.

[0029] In addition, the inventors found that if the proportion of the first coating layer in the lithium supplement is too small (that is, the percentage of boron in the matrix mass is too small), the OBO bonds in the lithium supplement are small, and the oxygen capture effect is not significantly improved; if the proportion of the second coating layer in the lithium supplement is too small (that is, the percentage of the spinel phase material in the matrix mass is too small), the promotion effect on lithium ion transmission is not obvious. If the proportion of the first coating layer and the second coating layer in the lithium supplement is too large, the matrix content will be reduced, and then the lithium supplement capacity will be reduced, and the battery cycle capacity retention rate will be reduced.

[0030] According to some preferred embodiments, the borate is lithium borate.

[0031] According to some preferred embodiments, the spinel phase material is selected from at least one of lithium nickel manganese oxide and lithium manganese oxide.

[0032] In a second aspect, the present invention provides a method for preparing the positive electrode lithium supplement agent according to the first aspect, the preparation method comprising:

[0033] The substrate is mixed with boric acid, and subjected to a first solid phase sintering to form a first coating layer on the surface of the substrate to obtain a first modified substrate;

[0034] The first modified matrix and the spinel phase material are mixed evenly, and subjected to a second solid phase sintering to form a second coating layer on the surface of the first coating layer to obtain a positive electrode lithium supplement.

[0035] The present invention first forms a borate coating layer (first coating layer) by solid-phase sintering boric acid and a substrate, introduces a stable chemical bond OBO bond on the surface of the substrate, and utilizes the electron-deficient property of B to form a coordination bond with oxygen, thereby capturing the oxygen released by the delithiation of Li5FeO4 during the first charging process, improving the impact of the subsequent side reaction between active oxygen and the electrolyte on the performance of the battery, and also reducing the residual alkali on the surface of the lithium supplement. Then, a spinel phase coating layer is coated on the surface of the borate coating layer (first coating layer). The spinel phase coating layer is used to prevent oxygen from diffusing out of the lithium supplement and avoid side reactions between active oxygen and the electrolyte. On the other hand, the three-dimensional lithium ion transmission channel of the spinel phase coating layer is used to promote rapid transmission of lithium ions and thus facilitate rapid lithium supplementation.

[0036] According to some preferred embodiments, the mass ratio of the matrix to boric acid is 100:0.5-1.8. The inventors found that if the amount of boric acid used is too small, it is not conducive to the formation of the first coating layer; a small amount of boric acid can only introduce a small number of OBO bonds on the surface of the matrix, which has a poor effect on oxygen capture and is not conducive to the reduction of residual alkali content. If the amount of boric acid used is too much, it will reduce the content of the matrix in the lithium supplement, resulting in a decrease in lithium supplement capacity and a decrease in the battery's cycle capacity retention rate. Therefore, the mass ratio of the matrix to boric acid in the present invention is preferably within the above range.

[0037] According to some preferred embodiments, the mass ratio of the first modified matrix to the spinel phase material is 100:0.1-0.3. The inventors have found that if the amount of spinel phase material is too small, it is not conducive to the formation of the second coating layer, and the promotion effect on lithium ion transmission is not obvious. If the amount of spinel phase material is too much, the content of the matrix in the lithium supplement will be reduced, resulting in a decrease in the lithium supplement capacity and a decrease in the battery's cycle capacity retention rate. Therefore, the mass ratio of the first modified matrix to the spinel phase material of the present invention is preferably within the above range.

[0038] According to some preferred embodiments, the first solid-phase sintering and the second solid-phase sintering are performed under a protective atmosphere, and the temperature of the second solid-phase sintering is lower than the temperature of the first solid-phase sintering; preferably, the protective atmosphere is an inert gas atmosphere, preferably a nitrogen atmosphere.

[0039] The temperature of the second solid phase sintering of the present invention is lower than that of the first solid phase sintering to ensure that the stability of the borate coating layer (first coating layer) and the substrate is not affected while generating a stable spinel coating layer (second coating layer).

[0040] It should be noted that the role of the protective gas in the present invention is to prevent water, carbon dioxide and the like in the air from reacting with the residual alkali on the surface of the substrate.

[0041] According to some preferred embodiments, the temperature of the first solid-phase sintering is 500-700°C (for example, it can be 500°C, 550°C, 600°C, 650°C or 700°C), preferably 600-650°C (for example, it can be 600°C, 610°C, 620°C, 630°C, 640°C or 650°C), and the time of the first solid-phase sintering is 10-30h (for example, it can be 10h, 12h, 14h, 16h, 18h, 20h, 22h, 24h, 26h, 28h or 30h), preferably 15-25h (for example, it can be 15h, 16h, 17h, 18h, 19h, 20h, 21h, 22h, 23h, 24h or 25h). The inventors found that if the sintering temperature is too low, the coating layer is not strong and the bonding force is relatively low, the formed OBO is unstable, and the subsequent oxygen capture effect is not good; if the sintering temperature is too high, the matrix particle size becomes larger, resulting in a decrease in surface activity and a subsequent oxygen capture effect is also not good. Therefore, the present invention preferably sets the temperature of the first solid phase sintering to the above range.

[0042] According to some preferred embodiments, the temperature of the second solid-phase sintering is 400-600°C (for example, it can be 400°C, 450°C, 500°C, 550°C or 600°C), preferably 450-550°C (for example, it can be 450°C, 460°C, 470°C, 480°C, 490°C, 500°C or, 510°C, 520°C, 530°C, 540°C or 550°C), and the time of the second solid-phase sintering is 10-40h (for example, it can be 10h, 12h, 14h, 16h, 18h, 20h, 22h, 24h, 26h, 28h, 30h, 32h, 34h, 36h, 38h or 40h), preferably 20-25h (for example, it can be 20h, 21h, 22h, 23h, 24h or 25h). The inventors have found that if the sintering temperature is too low, the bonding force between the second coating layer and the first coating layer is low, the spinel phase is unstable, the coating is not firm, and it is not conducive to the transmission of lithium ions. If the sintering temperature is too high, the particle size of the matrix will become larger, resulting in a decrease in surface activity, which is also not conducive to the subsequent lithium ion transmission. Therefore, the temperature of the second solid phase sintering is preferably within the above range.

[0043] In some preferred embodiments, the first solid-phase sintering temperature and the second solid-phase sintering temperature are relatively high within a preferred range, the unit cell of the lithium supplement agent is large, the stability of the coating layer is good, and the OBO bond in the lithium supplement agent is more stable. If the temperature is too high or too low, it is not conducive to the growth of the unit cell in the lithium supplement agent, thereby failing to ensure the ability of the OBO bond to capture oxygen and improve the comprehensive performance of the lithium supplement agent.

[0044] The present invention provides a positive electrode plate in a third aspect, wherein the positive electrode plate comprises the positive electrode lithium supplement agent described in the first aspect.

[0045] According to some preferred embodiments, the positive electrode lithium supplement accounts for 1 to 4 wt % in the positive electrode plate.

[0046] In some preferred embodiments of the present invention, the positive electrode plate comprises: positive electrode active material LiFePO4 accounts for 92-94wt%, positive electrode lithium supplement accounts for 1-4wt%; binder accounts for 1.8-2.3wt%, and conductive agent accounts for 1.2-1.8wt%.

[0047] The present invention provides a lithium-ion battery in a fourth aspect, comprising the positive electrode sheet described in the third aspect.

[0048] The lithium-ion battery assembled from the positive electrode sheet containing the lithium supplement provided by the present invention has excellent high-temperature storage gas production performance, high-temperature storage capacity retention rate and high-temperature cycle capacity retention rate.

[0049] In some preferred embodiments of the present invention, a lithium-ion battery comprises the above-mentioned positive electrode sheet, negative electrode sheet and separator.

[0050] In order to more clearly illustrate the technical solutions and advantages of the present invention, the present invention is further described below in conjunction with the embodiments. The present invention does not specifically limit the sources of the reagents used in the embodiments and comparative examples, and they can be directly purchased or synthesized by themselves. The Li5FeO4 matrix of the present invention can be directly purchased or prepared by yourself. The self-preparation of the Li5FeO4 matrix includes: weighing lithium hydroxide and nano-iron trioxide according to a molar ratio of Fe to Li element of 5.5:1 and mixing them evenly, heating to 850°C at 5°C / min in an oxygen atmosphere and keeping warm for 10h, then cooling to room temperature at 5°C / min, crushing, and passing through a 400m mesh sieve to obtain the Li5FeO4 matrix.

[0051] Example 1

[0052] A positive electrode lithium replenisher includes a positive electrode lithium replenisher with a double-layer coating, including a substrate, a first coating layer coated on the surface of the substrate, and a second coating layer coated on the surface of the first coating layer; wherein the substrate is Li5FeO4, the first coating layer is a borate coating layer, and the boron element in the borate coating layer accounts for 0.18% of the substrate mass; the second coating layer is a spinel phase material coating layer, and the spinel phase material coating layer accounts for 0.26% of the substrate mass.

[0053] The preparation method of the positive electrode lithium supplement comprises the following steps:

[0054] (1) Preparation of the first coating layer (borate coating layer): The Li5FeO4 matrix and boric acid in a mass ratio of 100:1 and anhydrous ethanol (dispersant) were mixed in a high-speed disperser at a speed of 35 rpm / min for 30 min, and then the mixed mixture was placed in a box furnace and nitrogen was introduced for high-temperature sintering. The high-temperature sintering procedure was as follows: heating to 650°C at 2°C / min and keeping the temperature for 15 h, and then cooling to room temperature at 2°C / min; after high-temperature sintering, the matrix was crushed and passed through a 400-m mesh sieve to obtain the first modified matrix (Li5FeO4 with a borate coating layer on the surface).

[0055] (2) Preparation of the second coating layer (spinel phase material coating layer): The prepared first modified substrate (Li5FeO4 substrate with a borate coating layer on the surface) and lithium nickel manganese oxide were placed in a high-speed disperser at a mass ratio of 100:0.26, and stirred at a speed of 40 rpm / min for 45 minutes for mixing. The mixed mixture was then placed in a box furnace and nitrogen was introduced for high-temperature sintering. The high-temperature sintering procedure was as follows: heating to 450°C at 1°C / min and keeping the temperature for 25 hours, and then cooling to room temperature at 1°C / min; after high-temperature sintering, the mixture was crushed and passed through a 400-m mesh sieve to obtain a positive electrode lithium supplement having a double coating layer (borate coating layer and spinel phase material coating layer).

[0056] A positive electrode sheet, with the mass of the positive electrode active material layer being 100%, the positive electrode active material LiFePO4 accounts for 94wt%, the positive electrode lithium supplement accounts for 2.5wt%, PVDF accounts for 2.0wt%, and the conductive agent accounts for 1.5wt%. The single surface density of the positive electrode active material layer is 20mg / cm 2 , the average compacted density is 2.5g / cm 3 .

[0057] Example 2

[0058] A positive electrode lithium replenisher includes a positive electrode lithium replenisher with a double-layer coating, including a substrate, a first coating layer coated on the surface of the substrate, and a second coating layer coated on the surface of the first coating layer; wherein the substrate is Li5FeO4, the first coating layer is a borate coating layer, and the boron element in the borate coating layer accounts for 0.18% of the substrate mass; the second coating layer is a spinel phase material coating layer, and the spinel phase material coating layer accounts for 0.26% of the substrate mass.

[0059] The preparation method of the positive electrode lithium supplement comprises the following steps:

[0060] (1) Preparation of the first coating layer (borate coating layer): The prepared Li5FeO4 matrix was mixed with boric acid and anhydrous ethanol (dispersant) in a mass ratio of 100:1 in a high-speed disperser at a speed of 35 rpm / min for 30 min. The mixed mixture was then placed in a box furnace and nitrogen was introduced for high-temperature sintering. The high-temperature sintering procedure was as follows: the temperature was raised to 600°C at 2°C / min and kept at this temperature for 15 h, and then the temperature was lowered to room temperature at 2°C / min. After high-temperature sintering, the matrix was crushed and passed through a 400-m mesh sieve to obtain the first modified matrix (Li5FeO4 with a borate coating layer on the surface).

[0061] (2) Preparation of the second coating layer (spinel phase material coating layer): The prepared first modified substrate (Li5FeO4 substrate with a borate coating layer on the surface) and lithium manganate were placed in a high-speed disperser at a mass ratio of 100:0.26, and stirred at a speed of 40 rpm / min for 45 minutes for mixing. The mixed mixture was then placed in a box furnace and nitrogen was introduced for high-temperature sintering. The high-temperature sintering procedure was: heating to 550°C at 1°C / min and keeping the temperature for 20 hours, and then cooling to room temperature at 1°C / min; after high-temperature sintering, the mixture was crushed and passed through a 400-m mesh sieve to obtain a positive electrode lithium supplement having a double coating layer (borate coating layer and spinel phase material coating layer).

[0062] A positive electrode sheet, with the mass of the positive electrode active material layer being 100%, the positive electrode active material LiFePO4 accounts for 94wt%, the positive electrode lithium supplement accounts for 1wt%, the PVDF accounts for 2.0wt%, and the conductive agent accounts for 1.5wt%. The single surface density of the positive electrode active material layer is 20mg / cm 2 , the average compacted density is 2.5g / cm 3 .

[0063] Example 3

[0064] A positive electrode lithium replenisher includes a positive electrode lithium replenisher with a double-layer coating, including a substrate, a first coating layer coated on the surface of the substrate, and a second coating layer coated on the surface of the first coating layer; wherein the substrate is Li5FeO4, the first coating layer is a borate coating layer, and the boron element in the borate coating layer accounts for 0.18% of the substrate mass; the second coating layer is a spinel phase material coating layer, and the spinel phase material coating layer accounts for 0.26% of the substrate mass.

[0065] The preparation method of the positive electrode lithium supplement comprises the following steps:

[0066] (1) Preparation of the first coating layer (borate coating layer): The prepared Li5FeO4 matrix was mixed with boric acid and anhydrous ethanol (dispersant) in a mass ratio of 100:1 in a high-speed disperser at a speed of 35 rpm / min for 30 min. The mixed mixture was then placed in a box furnace and nitrogen was introduced for high-temperature sintering. The high-temperature sintering procedure was as follows: the temperature was raised to 600°C at 2°C / min and kept at this temperature for 15 h, and then the temperature was lowered to room temperature at 2°C / min. After high-temperature sintering, the matrix was crushed and passed through a 400-m mesh sieve to obtain the first modified matrix (Li5FeO4 with a borate coating layer on the surface).

[0067] (2) Preparation of the second coating layer (spinel phase material coating layer): The prepared first modified substrate (Li5FeO4 substrate with a borate coating layer on the surface) and lithium manganate were placed in a high-speed disperser at a mass ratio of 100:0.26, and stirred at a speed of 40 rpm / min for 45 minutes for mixing. The mixed mixture was then placed in a box furnace and nitrogen was introduced for high-temperature sintering. The high-temperature sintering procedure was: heating to 550°C at 1°C / min and keeping the temperature for 20 hours, and then cooling to room temperature at 1°C / min; after high-temperature sintering, the mixture was crushed and passed through a 400-m mesh sieve to obtain a positive electrode lithium supplement having a double coating layer (borate coating layer and spinel phase material coating layer).

[0068] A positive electrode sheet, with the mass of the positive electrode active material layer being 100%, the positive electrode active material LiFePO4 accounts for 94wt%, the positive electrode lithium supplement accounts for 4wt%, the PVDF accounts for 2.0wt%, and the conductive agent accounts for 1.5wt%. The single surface density of the positive electrode active material layer is 20mg / cm 2 , the average compacted density is 2.5g / cm 3 .

[0069] Example 4

[0070] It is basically the same as Example 1, except that the boron element in the first coating layer accounts for 0.1% of the mass of the substrate, and the mass ratio of the Li5FeO4 substrate to boric acid in step (1) is 100:0.57.

[0071] Example 5

[0072] It is basically the same as Example 1, except that the boron element in the first coating layer accounts for 0.3% of the mass of the substrate, and the mass ratio of the Li5FeO4 substrate to the boric acid in step (1) is 100:1.72.

[0073] Example 6

[0074] It is basically the same as Example 1, except that the second coating layer accounts for 0.1% of the mass of the substrate, and the mass ratio of the first modified substrate to lithium nickel manganese oxide in step (2) is 100:0.1.

[0075] Example 7

[0076] It is basically the same as Example 1, except that the second coating layer accounts for 0.3% of the mass of the substrate, and the mass ratio of the first modified substrate to lithium nickel manganese oxide in step (2) is 100:0.3.

[0077] Example 8

[0078] The method is basically the same as Example 1, except that the high temperature sintering procedure in step (1) is as follows: heating to 700°C at 2°C / min and keeping the temperature for 10 hours, and then cooling to room temperature at 2°C / min.

[0079] Example 9

[0080] The method is basically the same as Example 1, except that the high temperature sintering procedure in step (1) is as follows: heating to 600°C at 2°C / min and keeping the temperature for 10 hours, and then cooling to room temperature at 2°C / min.

[0081] Example 10

[0082] The method is basically the same as Example 1, except that the high temperature sintering procedure in step (1) is as follows: heating to 500°C at 2°C / min and keeping the temperature for 10 hours, and then cooling to room temperature at 2°C / min.

[0083] Embodiment 11

[0084] The method is basically the same as Example 1, except that the high temperature sintering procedure in step (2) is as follows: heating to 600°C at 2°C / min and keeping the temperature for 10 hours, and then cooling to room temperature at 2°C / min.

[0085] Example 12

[0086] The method is basically the same as Example 1, except that the high temperature sintering procedure in step (2) is as follows: heating to 550°C at 2°C / min and keeping the temperature for 10 hours, and then cooling to room temperature at 2°C / min.

[0087] Example 13

[0088] The method is basically the same as Example 1, except that the high temperature sintering procedure in step (2) is as follows: heating to 400°C at 2°C / min and keeping the temperature for 10 hours, and then cooling to room temperature at 2°C / min.

[0089] Comparative Example 1

[0090] It is basically the same as Example 1, except that the positive electrode lithium supplement is Li5FeO4 lithium supplement and does not contain a coating layer.

[0091] Comparative Example 2

[0092] It is basically the same as Example 1, except that: the positive electrode material is Li5FeO4 with only a borate coating layer on the surface, and does not contain a spinel phase material coating layer; that is, the preparation method of the positive electrode lithium supplement does not include step (2).

[0093] Comparative Example 3

[0094] It is basically the same as Example 1, except that the positive electrode material is Li5FeO4, the surface of which is only coated with a spinel phase material coating layer, and does not include a borate coating layer.

[0095] Comparative Example 4

[0096] It is basically the same as Example 1, except that the first coating layer contains 0.05% of the mass of the boron element in the matrix, and the mass ratio of the Li5FeO4 matrix to the boric acid in step (1) is 100:0.3.

[0097] Comparative Example 5

[0098] It is basically the same as Example 1, except that the first coating layer contains 0.6% of the mass of the boron element in the matrix, and the mass ratio of the Li5FeO4 matrix to the boric acid in step (1) is 100:3.4.

[0099] Comparative Example 6

[0100] It is basically the same as Example 1, except that the second coating layer accounts for 0.03% of the mass of the substrate, and the mass ratio of the first modified substrate to lithium nickel manganese oxide in step (2) is 100:0.03.

[0101] Comparative Example 7

[0102] It is basically the same as Example 1, except that the second coating layer accounts for 0.6% of the mass of the substrate, and the mass ratio of the first modified substrate to lithium nickel manganese oxide in step (2) is 100:0.6.

[0103] Comparative Example 8

[0104] It is basically the same as Example 1, except that: (1) the high temperature sintering procedure during the preparation of the first coating layer (borate coating layer) is: heating to 500°C at 2°C / min and keeping it at that temperature for 15h, and then cooling to room temperature at 2°C / min.

[0105] (2) The high temperature sintering procedure during the preparation of the second coating layer (spinel phase material coating layer) is as follows: heating to 600°C at 1°C / min and keeping at that temperature for 25h, and then cooling to room temperature at 1°C / min.

[0106] The performance data of the positive electrode lithium replenisher prepared in each embodiment and comparative example of the present invention and the battery containing the positive electrode lithium replenisher are shown in Table 1. The method of each performance test is as follows:

[0107] Residual alkali content of positive electrode lithium supplement: tested in accordance with GB / T 41704-2022;

[0108] Battery performance:

[0109] Battery assembly: The positive electrode sheets, negative electrode sheets and separators (ceramic coated separators) prepared in the embodiments and comparative examples are assembled to obtain batteries, wherein the negative electrode active materials in the negative electrode sheets are graphite and silicon negative electrodes, and the negative electrode current collector is copper foil, and its compaction density is 1.5 g / cm 3 Among them, the mass of the negative electrode active material accounts for 96wt% of the negative electrode sheet, the conductive carbon black (SP) accounts for 1.0wt% of the negative electrode sheet, the sodium carboxymethyl cellulose (CMC) accounts for 1.0wt% of the negative electrode sheet, and the styrene-butadiene rubber (SBR) accounts for 2.0wt% of the negative electrode sheet.

[0110] High temperature storage gas production performance High temperature and storage capacity retention rate test: At 60℃, discharge at 1C constant current to 2.0V, rest for 10min, then charge at 1C constant current to 3.65V, and charge at constant voltage to 0.05C, rest for 10min;

[0111] 1C constant current discharge to 2.0V, rest for 10min, 1C constant current charge to 3.65V, and constant voltage to 0.05C, rest for 10min, measure the volume before storage; after 7 days of high temperature storage at 60℃, measure the volume after storage; 1C constant current discharge to 2.0V, rest for 10min, 1C constant current charge to 3.65V, and constant voltage to 0.05C, rest for 10min, measure the storage capacity retention rate. The percentage change of the volume after storage and the volume before storage is the high temperature storage gas production performance.

[0112] Test of 500-cycle high-temperature cycle capacity retention rate: At 45°C, charge at 1C constant current to 3.65V, charge at constant voltage to 0.05C, rest for 10 minutes, discharge at 1C constant current to 2.0V, rest for 10 minutes; repeat the above process for 500 weeks and measure the capacity retention rate.

[0113] Table 1. Residual alkali content of positive electrode lithium replenishers prepared in various embodiments of the present invention and comparative examples and performance data of batteries containing the positive electrode lithium replenishers

[0114]

[0115]

[0116] As can be seen from Table 1, the positive electrode lithium replenisher prepared in the embodiment of the present invention can capture the oxygen released by Li5FeO4 during lithium depletion, effectively improving the problems of battery gas production and poor high temperature performance caused by the release of oxygen during the existing Li5FeO4 lithium replenishment process, and improving the high temperature performance and cycle performance of the battery.

[0117] Compared with Example 1 of the present invention, Comparative Example 1 uses Li5FeO4 lithium supplement agent, and does not form the first coating layer and the second coating layer on the surface of Li5FeO4, and cannot effectively capture the oxygen released during the Li5FeO4 lithium supplement process, causing the active oxygen to react with the electrolyte, thereby significantly deteriorating the high-temperature storage gas production performance of the battery and significantly reducing the high-temperature storage capacity retention rate and the high-temperature cycle capacity retention rate.

[0118] In Comparative Example 2, only the first coating layer is formed on the surface of Li5FeO4, so that the high-temperature storage gas production performance of the battery containing the positive electrode lithium supplement is significantly improved compared with Comparative Example 1. Compared with Example 1, due to the lack of the second coating layer, it is impossible to effectively prevent oxygen from diffusing out of the lithium supplement and directly contacting the electrolyte. At the same time, the electrolyte has a certain degree of corrosion on the substrate and the first coating layer, resulting in a decrease in the high-temperature storage gas production performance, high-temperature storage capacity retention rate and high-temperature cycle capacity retention rate of the battery containing the positive electrode lithium supplement.

[0119] Compared with Example 1, Comparative Example 3 only forms a second coating layer on the surface of Li5FeO4, but because it does not have a first coating layer, it cannot effectively capture the oxygen released during the lithium replenishment process of Li5FeO4, resulting in a decrease in the high-temperature storage gas production performance, high-temperature storage capacity retention rate, and high-temperature cycle capacity retention rate of the battery containing the positive electrode lithium replenisher. Compared with Example 1, the amount of boric acid used in Comparative Example 4 is too low, that is, the electron-deficient B content is too low, the OBO bonds are too few, and the ability to capture oxygen is limited. The high-temperature storage gas production performance, high-temperature storage capacity retention rate, and high-temperature cycle capacity retention rate of the battery containing the positive electrode lithium replenisher are all reduced. Compared with Comparative Example 1, the high-temperature storage gas production performance, high-temperature storage capacity retention rate, and high-temperature cycle capacity retention rate of the battery containing the positive electrode lithium replenisher are not significantly improved in Comparative Examples 3 and 4.

[0120] Compared with Example 1, the content of the first coating layer or the second coating layer formed on the surface of Li5FeO4 in Comparative Examples 5 and 7 is too high, which will lead to too low content of the Li5FeO4 matrix in the positive electrode lithium supplement, thereby affecting the high temperature storage capacity retention rate and high temperature cycle capacity retention rate of the battery.

[0121] Compared with Example 1, the amount of spinel phase material used in Comparative Example 6 is too low, which is not conducive to forming a stable second coating layer, and cannot effectively prevent oxygen from diffusing out of the lithium replenisher, thereby avoiding direct contact between oxygen and the electrolyte, resulting in a decrease in the high-temperature storage capacity retention rate and high-temperature cycle capacity retention rate of the battery containing the positive electrode lithium replenisher.

[0122] Compared with Example 1, the solid-phase sintering temperature of the second coating layer in Comparative Example 8 is higher than the solid-phase sintering temperature of the first coating layer, which will cause the excessively high temperature to destroy the already formed first coating layer, thereby affecting the stability of the first coating layer and causing the OBO bond to be unstable, resulting in a reduction in the ability of the lithium supplement agent to capture oxygen, etc., and further causing the performance of the battery to deteriorate.

[0123] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A positive electrode lithium supplement, characterized in that: The positive electrode lithium supplement comprises a substrate and a coating layer coated on the surface of the substrate; the coating layer comprises a first coating layer coated on the surface of the substrate and a second coating layer coated on the surface of the first coating layer; The substrate is Li5FeO4; the first coating layer is borate, and the second coating layer is spinel phase material; the boron element in the first coating layer accounts for 0.1-0.3% of the mass of the substrate, and the second coating layer accounts for 0.1-0.3% of the mass of the substrate.

2. The positive electrode lithium supplement according to claim 1, characterized in that: The borate is lithium borate; and / or The spinel phase material is selected from at least one of lithium nickel manganese oxide and lithium manganese oxide.

3. A method for preparing a positive electrode lithium supplement according to any one of claims 1 to 2, characterized in that: The preparation method comprises: The substrate is mixed with boric acid, and subjected to a first solid phase sintering to form a first coating layer on the surface of the substrate to obtain a first modified substrate; The first modified matrix and the spinel phase material are mixed evenly, and subjected to a second solid phase sintering to form a second coating layer on the surface of the first coating layer to obtain a positive electrode lithium supplement.

4. The preparation method according to claim 3, characterized in that: The mass ratio of the matrix to the boric acid is 100:0.5-1.

8.

5. The preparation method according to claim 3, characterized in that: The mass ratio of the first modified matrix to the spinel phase material is 100:0.1-0.

3.

6. The preparation method according to claim 3, characterized in that: The first solid-phase sintering and the second solid-phase sintering are performed under a protective atmosphere, and the temperature of the second solid-phase sintering is lower than the temperature of the first solid-phase sintering; preferably, the protective atmosphere is an inert gas atmosphere, preferably a nitrogen atmosphere.

7. The preparation method according to claim 6, characterized in that: The temperature of the first solid phase sintering is 500-700° C., preferably 600-650° C., and the time of the first solid phase sintering is 10-30 hours, preferably 15-25 hours; and / or The temperature of the second solid-phase sintering is 400-600° C., preferably 450-550° C., and the time of the second solid-phase sintering is 10-40 hours, preferably 20-25 hours.

8. A positive electrode sheet, characterized in that: The positive electrode plate comprises the positive electrode lithium supplement agent according to any one of claims 1 to 2.

9. The positive electrode sheet according to claim 8, characterized in that: The positive electrode lithium supplement accounts for 1 to 4 wt % of the positive electrode plate.

10. A lithium ion battery, characterized in that: The positive electrode sheet comprises the positive electrode sheet as described in any one of claims 8 to 9.

Citation Information

Patent Citations

  • Lithium ion battery negative pole pre-lithiation method and lithium ion battery

    CN109546226A

Cited By

  • Low-gas-production iron-based composite lithium supplementing material and preparation method thereof, lithium ion battery and electric equipment

    CN121215737A

  • Lithium supplement additive for high-capacity and high-stability lithium ion battery and preparation method of lithium supplement additive

    CN122552662A